Massive OB stars at varying Z. Issue Volume 9:Issue S307(2014) (23rd January 2015) - Herrero, A.; Garcia, M.; Simón-Díaz, S.; Camacho, I.; Sabín-Sanjulián, C.; Castro, N.
Abstract: Massive stars play a key role in environments with very different metallicities. To interpret the role of massive stars in these systems we have to know their properties at different metallicities. The Local Group offers an excellent laboratory to this aim.